High-Performance Liquid Chromatography Analysis of Caffeine and Trigonelline in Instant Coffee: A Malaysian Market Study - Lee, Yen Mae; Cheng, Cherlyn Chen Xia; Lai Chun Wong (Malaysian Journal of Science (MJS), 2025)
Caffeine and trigonelline are the main alkaloids found in coffee that play a significant role to its quality and impact on human well-being. However, exceeding the recommended intake can yield negative effects. In this study, a reverse phase high-performance liquid chromatography technique was validated for the concurrent quantification of caffeine and trigonelline within instant coffee products. The chromatographic separation was executed employing a GraceSmart RP C18 column under gradient elution consisting of water and methanol as the mobile phase, and heptafluorobutyric acid as an ion pairing agent. The validated method was utilised to determine the caffeine and trigonelline content in fifteen products, revealing concentrations ranging from 2.02 to 47.54 mg/g for caffeine and 0.37 to 11.00 mg/g for trigonelline. On a per-serving basis, this equated to 36.43–183.33 mg of caffeine and 6.70–41.41 mg of trigonelline. While the caffeine content per serving adhered to FDA safety guidelines, the potential for exceeding recommended daily intake of 400 mg was identified with multiple servings. Furthermore, one product exhibited a caffeine level only at 50.5% of its label claim. This study contributes valuable data on the caffeine and trigonelline content of Malaysian instant coffee, emphasizing the importance of accurate labelling and informed consumer choices.